Western Trends of Human Resources Management: Theories and Practices - Andalib, Tarnima Warda (Penerbit Universiti Malaysia Pahang, 2015)
Western Human Resources Management (HRM) policies are influenced by certain sets of external and internal factors and divergent developed models. Nevertheless, while building up the human resources management models certain researchers have concentrated on humanitarian ground whereas others have considered human resources only as one of the tools. The practitioners chose the most beneficial HRM policy for their organizations. The authors have dicusssed about the influential factors that affect to build the models. These models those have been discovered and recognized at different times are also discussed in this paper. Finally, the influential factors and used models of the western HRM practices have been found and analyzed.